Advocacy in the system of free legal aid - Chudyk Nataliіa (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article describes the role of the Bar in the system of free legal aid provision. The principle of protection and priority of human and civil rights and freedoms is the most important principle of any state governed by the rule of law, which proclaims the priority of human and civil rights and freedoms and establishes the limits of administrative law. States undertake to comply with international human rights standards historically achieved. A democratic state and civil society cannot exist without the effective functioning of an independent and strong bar. The Bar is able to significantly influence all aspects of the state’s life, actively contribute to the implementation of reforms and the formation of the rule of law. The process of optimising the functioning of the legal aid system in Ukraine requires synchronised reform of both special substantive and procedural legislation. After all, the effectiveness of ensuring and exercising the right to free legal aid depends primarily on the quality, perfection and efficiency of the legal framework in this area, the constant improvement of its norms and provisions, which would take into account new challenges, opportunities and prospects, and meet the current needs of vulnerable segments of society.